Parenting in a Pandemic: Preliminary Support for Delivering Brief Behavioral Parent Training Through Telehealth. Issue 1 (January 2023) - Holzman, Jacob B. W.; Hawks, Jessica L.; Kennedy, Sarah M.; Anthony, Bruno J.; Anthony, Laura G.
Behavioral problems, such as noncompliance and aggression, are a common referral reason to mental health services for young children. Behavioral parent training (BPT) is the leading intervention for addressing behavioral problems and leads to benefits in a variety of parental factors (e.g., parenting efficacy and parenting stress). While the COVID-19 pandemic dramatically shifted service delivery toward telehealth services, limited work has evaluated the effectiveness of BPT when delivered in a brief, group format through telehealth. The current retrospective chart review study evaluated the engagement to and preliminary effectiveness of a brief version of BPT delivered through telehealth to 64 families of 3- to 7-year-olds referred for behavioral problems. Families attended an average of 4.55 of 6 sessions and most families had two caregivers who engaged in the intervention. Significant reductions in caregivers' report of children's behavioral problems and improvements in parenting self-efficacy resulted. Future research and clinical implications are discussed.